A Dutch report on the ethics of neonatal care: a commentary. Issue 1 (February 1995) - Rivers, RPA
Abstract : The moral arguments and the decision-making processes arising from them in the context of the dilemmas that arise in considering the appropriateness and implementation of withholding or withdrawing treatment in certain neonates form the basis of this commentary. It is concluded that the differing opinions on management of these babies by individual paediatricians results from their differing moral outlooks rather than from any incoherence in the moral arguments set out in the Dutch report.